1996
DOI: 10.3758/bf03206820
|View full text |Cite
|
Sign up to set email alerts
|

Structure from motion: A tolerance analysis

Abstract: For a proper evaluation of the performance of the visual system one needs to analyze the stimuli. From such an analysis it should become clear whether the information required for a certain task is available and to what extent. If we do not perform such an analysis we cannot decide whether the limits reached by the visual system are set by stimulus limitations or by limits of the visual system. Koenderink and van Doorn (1987) performed a tolerance analysis to measure the extent to which certain information is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…In order to assess the actual extent of3-D structural deformation depicted in these constant flow field displays, it is useful to employ a tolerance analysis that has recently been developed by Hogervorst, Kappers, and Koenderink (1996) to test the rigidity of an object's projected motion after it has been transformed to a pattern of parallel trajectories by the removal ofimage rotation. The basic idea is quite simple and powerful.…”
Section: Methodsmentioning
confidence: 99%
“…In order to assess the actual extent of3-D structural deformation depicted in these constant flow field displays, it is useful to employ a tolerance analysis that has recently been developed by Hogervorst, Kappers, and Koenderink (1996) to test the rigidity of an object's projected motion after it has been transformed to a pattern of parallel trajectories by the removal ofimage rotation. The basic idea is quite simple and powerful.…”
Section: Methodsmentioning
confidence: 99%
“…Still, using the planarity constraint is often sufficient to discriminate rigid from nonrigid transformations. More details about this method can be found in Hogervorst et al (1996). ,r n ) and (l/>l' ... , l/>n).…”
Section: Additional Constraintsmentioning
confidence: 99%
“…In some ofthe experiments of Norman and Todd (1993), subjects perceived a rigidly moving object even though they were looking at the projections of a nonrigidly moving object. We (Hogervorst, Kappers, & Koenderink, 1996) have shown that in those cases, the projections were very similar to those of a rigidly moving object. The visual system is apparently biased toward perceiving rigidly moving objects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Humans seem to be quite good at disentangling shape changes from object motion and characterizing motion as tumbling, rolling, swaying, stretching, leaping, spinning, flapping, dancing, kicking, bucking, jerking, sliding, gliding, tripping, or shaking. A large number of studies have examined human perception of rigid 3D shapes from motion cues (1)(2)(3)(4)(5); however, very few have examined nonrigid shape perception (6)(7)(8), and these have not dealt with what shapes are perceived.…”
mentioning
confidence: 99%